Catheter Ablation of Refractory Ventricular Fibrillation Storm After Myocardial Infarction: A Multicenter Study. Issue 20 (14th May 2019) - Komatsu, Yuki; Hocini, Mélèze; Nogami, Akihiko; Maury, Philippe; Peichl, Petr; Iwasaki, Yu-ki; Masuda, Keita; Denis, Arnaud; Voglimacci-Stephanopoli, Quentin; Wichterle, Dan; Kawamura, Mitsuharu; Fukamizu, Seiji; et al.
Abstract : Background: Ventricular fibrillation (VF) storm after myocardial infarction (MI) is a life-threatening condition that necessitates multiple defibrillations. Catheter ablation is a potentially effective treatment strategy for VF storm refractory to optimal medical treatment. However, its impact on patient survival has not been verified in a large population. Methods: We conducted a multicenter, retrospective observational study involving consecutive patients who underwent catheter ablation of post-MI refractory VF storm without preceding monomorphic ventricular tachycardia. The target of ablation was the Purkinje-related ventricular extrasystoles triggering VF. The primary outcome was in-hospital and long-term mortalities. Univariate logistic regression and Cox proportional-hazards analysis were used to evaluate clinical characteristics associated with in-hospital and long-term mortalities, respectively. Results: One hundred ten patients were enrolled (age, 65±11years; 92 men; left ventricular ejection fraction, 31±10%). VF storm occurred at the acute phase of MI (4.5±2.5 days after the onset of MI during the index hospitalization for MI) in 43 patients (39%), the subacute phase (>1 week) in 48 (44%), and the remote phase (>6 months) in 19 (17%). The focal triggers were found to originate from the scar border zone in 88 patients (80%). During in-hospital stay after ablation, VF storm subsided in 92 patients (84%). Overall, 30 (27%) in-hospital deaths occurred. The duration from the VF occurrence to the ablation procedure was associated with in-hospital mortality (odds ratio for each 1-day increase, 1.11 [95% CI, 1.03–1.20]; P =0.008). During follow-up after discharge from hospital, only 1 patient developed recurrent VF storm. However, 29 patients (36%) died, with a median survival time of 2.2 years (interquartile range, 1.2–5.5 years). Long-term mortality was associated with left ventricular ejection fraction <30% (hazard ratio, 2.54 [95% CI, 1.21–5.32]; P =0.014), New York Heart Association class ≥III (hazard ratio, 2.68 [95% CI, 1.16–6.19]; P =0.021), a history of atrial fibrillation (hazard ratio, 3.89 [95% CI, 1.42–10.67]; P =0.008), and chronic kidney disease (hazard ratio, 2.74 [95% CI, 1.15–6.49]; P =0.023). Conclusions: In patients with MI presenting with focally triggered VF storm, catheter ablation of culprit triggers is lifesaving and appears to be associated with short- and long-term freedom from recurrent VF storm. Mortality over the long-term follow-up is associated with the severity of underlying cardiovascular disease and comorbidities in this specific patient population. Abstract : Supplemental Digital Content is available in the text.